Forensic Assertive Community Treatment: Recidivism, hospitalization, and the role of housing and support. Issue 5 (3rd September 2017) - Kelly, Brian L.; Barrenger, Stacey L.; Watson, Amy C.; Angell, Beth
ABSTRACT: While Assertive Community Treatment (ACT) is considered an evidence-based service model, there is limited evidence regarding the effectiveness of an adaptation of the model, Forensic Assertive Community Treatment (FACT), for persons with serious mental illness who also have significant criminal justice system involvement. Using a multimethod approach, this article combines quantitative and qualitative data to review baseline information and nine-month follow-up recidivism, hospitalization, and housing outcomes for individuals enrolled in a FACT program. Findings suggest substance use, housing, and FACT team members' support played an important role in clients' prison reentry experiences.